Investigation of Nano Silica Ball Core-Poly(Styrene-Acrylonitrile-Methyl Methacrylate) Shell Hybrid Compounds - Chang Kim, Heon; Hyun Choi, Ki; Kyu Park, Seung (Asian Journal of Chemistry, 2012)
Silica core-copolymer shell hybrid compounds have been synthesized by copolymerization of styrene, acrylonitrile (AN) and methyl methacrylate (MMA) on the surface of g-methacryloxy propyl trimethoxy silane (g-MPS) modified nano silica ball (NSB). The core-shell materials were characterized by scanning electron microscope, Fourier transform infrared spectroscopy and thermo gravimetric analysis. The results show that the particle size distribution of new core-shell structured materials can be tuned by control of the core and the shell contents. The core-shell hybrid materials can also be adjusted to form the only one single spherical phase with the diameter of 200 nm. The addition of the core-shell hybrid materials to clearcoat enhances the anti scratch property.